Peningkatan Praktik Ekonomi Sirkular Minyak Jelantah Berbasis Masyarakat di Kota Salatiga - Istiyani, Ambar; Putra, Yanuar Surya; Riyanti, Budi (Penerbit Goodwood, 2025)
Purpose: This Community Service Activity aimed to enhance the Community-Based Circular Economy Practice of Used Cooking Oil in Salatiga City, Central Java. The goal was to develop new valuable goods and support the renewable energy raw material supply chain. Methodology: The method involved socializing the importance of the circular economy practice of used cooking oil and educating the participating waste banks about the supply chain in Salatiga. Training was also provided on making soap and candles as valuable products from used cooking oil. Monitoring and evaluation were conducted to assess the impact of the program. Results: The results showed that 27 out of 35 active waste banks in Salatiga City, which were the target of the program, had carried out used cooking oil collection activities and supported the used cooking oil circular economy supply chain. This indicates that the activity achieved its goal of at least 75% of waste bank units in Salatiga City participating in the circular economy practice of used cooking oil. Conclusions: The high use of cooking oil by Indonesian people results in a high potential volume of used cooking oil. Limitations: While the community service activity involved waste banks as participants, a key limitation was its narrow focus. To truly enhance the circular economy practices for used cooking oil, there is an urgent need to also provide socialization and training to the broader group of business actors who consume large quantities of cooking oil. Contribution: This community-led initiative demonstrates the implementation of a local circular economy model, offering invaluable insights to guide future efforts in promoting community-driven recycling and reuse of used cooking oil.